2020
DOI: 10.1021/acsptsci.0c00161
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ACE2–RBD Interaction as a Platform for COVID-19 Therapeutics: Development and Drug-Repurposing Screen of an AlphaLISA Proximity Assay

Abstract: The COVID-19 pandemic, caused by SARS-CoV-2, is a pressing public health emergency garnering a rapid response from scientists across the globe. Host cell invasion is initiated through direct binding of the viral spike protein to the host receptor angiotensin-converting enzyme 2 (ACE2). Disrupting the spike protein–ACE2 interaction is a potential therapeutic target for treating COVID-19. We have developed a proximity-based AlphaLISA assay to measure the binding of SARS-CoV-2 spike protein receptor binding domai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 23 publications
0
81
0
Order By: Relevance
“…Figure 6 shows representative compounds from some of the scaffolds/clusters. Out of these 319 clusters, 5 clusters contain compounds similar to already known inhibitors of RBD:hACE2 or SARS-CoV2 viral growth from the two published experimental studies [ 25 , 46 ], while all the remaining 314 clusters represent the novel classes of compounds identified with potential to target RBD:hACE interaction. Cluster 120 consisting of 2 compounds shares similarity with Paredrine (4-(2-Aminopropyl)phenol) which has been used as an eye solution for dilation of pupils and controls the release of aqueous humor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 shows representative compounds from some of the scaffolds/clusters. Out of these 319 clusters, 5 clusters contain compounds similar to already known inhibitors of RBD:hACE2 or SARS-CoV2 viral growth from the two published experimental studies [ 25 , 46 ], while all the remaining 314 clusters represent the novel classes of compounds identified with potential to target RBD:hACE interaction. Cluster 120 consisting of 2 compounds shares similarity with Paredrine (4-(2-Aminopropyl)phenol) which has been used as an eye solution for dilation of pupils and controls the release of aqueous humor.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike single protein targets, additional complexity associated with flat interaction interfaces of PPIs [ 4 ] and lack of a reference small molecule substrate or native ligand to guide the search strategy, pose major challenges for prediction of modulators of PPIs by docking. Availability of experimentally validated data set of 25 inhibitors for RBD_hACE and a set of 250 compounds which do not inhibit RBD_hACE2 interactions [ 25 ] gave us the opportunity to evaluate the performance of a docking approach for this PPI. Docking of these compounds on to the interaction interface of RBD using OpenEye software revealed that out of the 25 inhibitors (binders to RBD) in positive data set, 16 compounds docked to the site with docking score in the range of −2 to −3 kcal/mol, while remaining nine compounds were rejected as potential binders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanson et al, performed drug repurposing of 3384 small molecule drugs with 25 hits using a proximity-based assay that measures the binding of SARS-CoV-2 RBD and ACE2 ( Hanson et al, 2020 ). Even though the unbound states of the S protein and ACE2 lacks druggable pockets, there are well-defined pockets in the bound states for drug development.…”
Section: Targeting the S Proteinmentioning
confidence: 99%
“…These models were developed using experimental data generated by the following assays: the SARS-CoV-2 cytopathic effect (CPE) assay and its host cell cytotoxicity counterscreen, the Spike-ACE2 protein-protein interaction (AlphaLISA) assay and its TruHit counterscreen, the angiotensin-converting enzyme 2 (ACE2) enzymatic activity assay, the 3C-like (3CL) proteinase enzymatic activity assay, the SARS-CoV pseudotyped particle entry (CoV-PPE) assay and its counterscreen, the Middle-East respiratory syndrome coronavirus (MERS-CoV) pseudotyped particle entry assay (MERS-PPE) and its counterscreen and the human fibroblast toxicity (hCYTOX) assay. Such assays represent five distinct categories: viral entry (CPE 1 and host cell cytotoxicity counterscreen 2 ), viral replication (3CL enzymatic activity), live virus infectivity (AlphaLISA, TruHit counter screen, and ACE2 enzymatic activity) 3 , in vitro infectivity (coronavirus pseudotyped particle entry, PPE, with associated counter screens for two other coronaviruses, SARS-CoV and MERS) and human fibroblast cytotoxicity (hCYTOX), respectively, as described in the National Center for Advancing Translational Sciences (NCATS) COVID-19 portal. 4 We retrieved these datasets from the NCATS COVID-19 portal.…”
mentioning
confidence: 99%